Sonographically Guided Aspiration Cytology of Neck Nodes for Selection of Treatment and Follow-up in Patients with N0 Head and Neck Cancer - van den Brekel, Michiel W.M.; Reitsma, Laurens C.; Quak, Jasper J.; Smeele, Ludi E.; C, Johannes; Linden, van der; Snow, Gordon B.; Castelijns, Jonas A. (American Journal of Neuroradiology, 1999)
BACKGROUND AND PURPOSE: The management of the clinically negative neck (N0) remains controversial because the incidence of occult metastases is high and the prognostic difference between elective treatment and a “wait and see” approach remains unclear. This study was undertaken to assess the role of sonographically guided aspiration cytology for the selection of the initial-management strategy for the neck and for the early detection of neck metastases during follow-up of patients with N0.METHODS: Seventy-seven clinically and cytologically confirmed N0 patients, who underwent a transoral tumor excision and no neck treatment, were followed up for 1 to 4 years by both palpation and sonographically guided aspiration cytology.RESULTS: Fourteen patients (18%) had recurrent neck tumor; 10 (71%) of these necks were salvaged. Of the 14 neck failures, six were detected before being palpable and nine were detected within 7 months. Eleven of the 19 aspirated tumor-positive nodes had a minimal diameter smaller than 1 cm, and all four patients who eventually died had lymph node metastases larger than 14 mm.CONCLUSION: With sonographically guided aspiration cytology, the risk of missing occult metastases was 18%, which is less than expected after palpation only. Sonographically guided aspiration cytology is an effective technique for following up on the status of the neck after transoral tumor excision, and should be used at frequent intervals if no elective neck treatment is performed.